Effectiveness of government environmental auditing in the industrial manufacturing structure upgradation - Chai, Kuang-Cheng; Zhu, Jiawei; Lan, Hao-Ran; Lu, Yujiao; Liu, Rui-Yang; Liu, Pingshan (Frontiers in Environmental Science, 2022)
This paper is based on "Opinion of the Audit-Commission on Strengthening Resource and Environmental Auditing" issued by the Audit Commission in 2009. The commission suggested studies on the impact of industrial structure upgradation in the manufacturing enterprises in China, based on 2006 to 2008 stocks of the listed companies in Shanghai and Shenzhen. Propensity Score Matching (PSM) and Differences-in-Differences (DID) were used to test the induced effect of the policy on industrial structure upgradation by comparing the experimental and control groups before and after policy implementation. The study found that government environmental auditing (GEA) upgrades the structure of the manufacturing industry. The data also reveals that the positive impact of GEA on the upgradation of industrial structure was significantly manifested in state-owned enterprises (SOEs). The findings validate the governance effect of GEA, expand the perspective of industrial structure upgradation in manufacturing enterprises, and provide suggestions on the regulatory effect in the industrial transformation of enterprises.